Effect of periodontal therapy on circulating levels of endotoxin in women with periodontitis: A pilot clinical trial - Shaju P Jacob; Sonia Nath; R M Zade (Wolters Kluwer Medknow Publications, 2012)
Context: Periodontitis is a potential risk factor for adverse pregnancy outcomes due to the presence of a subgingival load of pathogenic bacteria. Instrumentation of periodontal pockets during treatment may result in bacteremia and/or endotoxemia. Aims: The aim of this pilot clinical trial was to determine the immediate post-scaling and root planing (SRP) level of circulating endotoxin in females presenting with chronic periodontitis. Settings and Design: A before-and-after pilot clinical trial among rural women of low socioeconomic status attending the outpatient department (OPD) for periodontitis. Materials and Methods: Twenty-four women aged 25-35 years, with at least five teeth having probing depth (PD) ≥5 mm, were selected for the study. The clinical trial was divided into three phases: phase 0 (screening), phase I (just before scaling), and phase II (15 min after scaling). Phase 0, one day prior to SRP, was used to assess the eligibility of the patients and record the periodontal status. Endotoxin levels were assessed by a semiquantitiative gel-clot assay, the limulus amoebocyte lysate (Lonza®), at phase I and phase II. Statistical analysis used: The Chi-square test was used for statistical analysis. Results: There was significant increase of endotoxins levels (P<.05) immediately after scaling (15 min). Conclusions: SRP can lead to endotoxemia, possibly by release of endotoxins by bacteria of periodontal origin, into the systemic circulation.